Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s11434-011-4782-7
|View full text |Cite
|
Sign up to set email alerts
|

Work toughening effect in Zr41Ti14Cu12.5Ni10Be22.5 bulk metallic glass

Abstract: Work hardening is a well-known phenomenon occurring in crystalline metals during deformation, which has been widely used to increase the strength of metals although their ductility is usually reduced simultaneously. Here we report that the plastic strain of Zr 41 Ti 14 Cu 12.5 Ni 10 Be 22.5 (at.%) bulk metallic glasses has been increased from 0.3% for the as-cast sample to 2.5%-8.0% for samples that have experienced pre-deformation under constrained conditions. The pre-deformed glassy alloys possess more free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…For conventional crystalline alloys, after plastic deformation, the microstructure can be changed (e.g., dislocation density), and the flow behaviors can be quite different. For BMGs, pre-plastic deformation is supposed to introduce microstructural inhomogeneities and induce controlled stress distributions or activate multiple shear bands, which are beneficial to enhancing the room temperature plasticity [183,184]. Huang et al utilized prior compressive plastic deformation to tune the room temperature plasticity of Ti 40 Zr 25 Ni 3 Cu 12 Be 20 BMG [185].…”
Section: Nanocrystallizationmentioning
confidence: 99%
“…For conventional crystalline alloys, after plastic deformation, the microstructure can be changed (e.g., dislocation density), and the flow behaviors can be quite different. For BMGs, pre-plastic deformation is supposed to introduce microstructural inhomogeneities and induce controlled stress distributions or activate multiple shear bands, which are beneficial to enhancing the room temperature plasticity [183,184]. Huang et al utilized prior compressive plastic deformation to tune the room temperature plasticity of Ti 40 Zr 25 Ni 3 Cu 12 Be 20 BMG [185].…”
Section: Nanocrystallizationmentioning
confidence: 99%
“…Tensile deformation of metallic glasses is typically marked by elastic loading followed by catastrophic failure via shear localization within a narrow region called a shear band . Substantial efforts have been made to alleviate brittle behavior by various toughening mechanisms. One possibility is to reduce the specimen size to below some critical dimension on the order of ∼100 nm, where metallic glasses have been reported to undergo a size-induced brittle to ductile transition in compression and in tension. , The origin of this transition is still being pursued because the experimental results are inconsistent with some literature reporting this transition to occur at 400, 200, and 100 nm , or not seeing any suppression of catastrophic failure even for sample sizes down to 150–300 nm. Most of the existing literature on nanomechanical deformation of individual metallic glass nanostructures describes experiments on samples fabricated using a focused ion beam (FIB). This milling technique irradiates the sample surface with a relatively high-energy ion beam, which can potentially lead to a modification of the local atomic arrangements or even to surface crystallization. Molecular dynamics (MD) simulations by Xiao et al revealed that ion bombardments suppressed shear band formation in 106.4 eV-irradiated Zr-based metallic glass nanowires (7.8 nm in diameter and 17.7 nm in length) .…”
mentioning
confidence: 99%
“…The result is a delightful one. We have 17 papers collected in this special issue, which cover broad areas of amorphous alloys, including atomic packing and clusters formation in amorphous alloys [1-3], fragility in glass-forming liquid [4], effects of alloying elements on the glass forming ability of different alloys [5][6][7], deformation behavior and improved mechanical property of amorphous alloys [8][9][10][11], glass-based composites [12,13], high strength metallic glass [14] and functional properties of metallic glasses [15][16][17].…”
Section: Amorphous Alloys -A Kind Of Promising High-performance Matermentioning
confidence: 99%